Let's talk about the role and impact of Social Computing in our lives - Oliveira, Jonice (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2020)
Social Computing refers to digital systems that support social interactions. The use of online social networks is intensifying every day, increasing the number of users and the different ways of content access. Collaborative platforms are growing and expanding their use, from basic health care to entrepreneurship. What are the new users' behaviors? What do they look for? How do they interact? Computing is increasingly present in social relationships. Consequently, social relationships have changed the way Computing is done. We can chat with other people who are physically distant or discover new resources and a range of services. Can events be identified only by monitoring social media? Can we use online social networks to promote citizens' participation in the decisions of a community or city? What is behind people's access to online social networks? How are transparency, filter bubbles, echo chambers, bias, and users' addiction issues handled? Can human behavior be modeled, simulated, and predicted? What are the precautions that users need to take? Trying to answer these questions, we will show some works developed by the Laboratory of Social Computing and Network Analysis (Lab CORES).